Parental and municipal school choice in the case of children receiving support - Lempinen, Sonia (My University, 2018)
This dissertation is positioned at the intersection of sociological studies on school choice and studies on educational support systems. The research in this dissertation focuses on the school choices by parents whose children receive support in first or seventh grade of comprehensive education and the organisation of comprehensive education in the municipalities where the participants live. This dissertation consists of four articles on parents’ views of children’s schooling or student allocation by social class, gender and level of support. Additionally, discussion of the results in relation to each other and the broader context of the organisation of comprehensive education. The first study (study 1) consists of three case studies of children diagnosed with ADHD (Attention Deficit Hyperactivity Disorder) and of interviews with the children, their parents and teachers to uncover these stakeholders’ views on the appropriate settings for these children. The second study (study 2) analyses registry data on one municipality’s allocation of seventh graders to classrooms (i.e. special education, regular and selective classrooms) by gender, ethnicity and level of support. The third and fourth studies (studies 3 and 4) examine the results of a questionnaire on schooling choices, support level and social class completed by the parents. Finally, the dissertation reports findings from interviews with the comprehensive education directors of the different municipalities where the parents in the studies live. To summarize, the articles encompassed in the thesis examine the choices by parents of children with support needs, while the overall dissertation focuses on the organisation of comprehensive education to understand actual inclusion and exclusion in the organisation and structure of the Finnish comprehensive education system. The results show that some municipalities use the school choice space – institutional (e.g. Varjo & Kalalahti, 2011) and social (Kosunen, 2016) –, and others do not; consequently, the organisation of comprehensive education varies across municipalities. Some municipalities lean more towards the adhocracies described by Skrtic (1991a; 1991b; 1995a; 1995b; 1995c), in which children are educated together regardless of their differences. The preliminary investigation of these municipalities studied shows that this shift is not motivated only by cost effectiveness. The organisation of comprehensive education in other municipalities tends to polarise children’s educational paths, offering more selective classes and special schools and classrooms. Furthermore, the findings indicate strong belief in the Finnish school system among the study informants as the majority of parents are satisfied with the support that their children receive and their children’s school allocations. The most important consideration for all parents is that their children be educated in neighbourhood schools to be able to socialise and function near home. The less support the children receive, the more important neighbourhood school allocation is to the parents. Most dissatisfaction with schooling among the families in this study is with allocation of children to schools or classrooms the parents do not want their children to attend. Not many parents had chosen selective classes or to live in certain neighbourhoods to access certain catchment areas, however those parents who did, had mostly an upper-class background. In addition, four types of comprehensive education organisation (inclusive, (small) traditional, traditional segregated and centralised) are identified. The complex differences in how municipalities organise comprehensive education are not necessarily visible to parents. During the dual system (general support and special support) implemented before 2010, children with special support needs were mostly segregated into special schools and classrooms, and other children stayed in general education classrooms in neighbourhood schools. Today, the allocations to neighbourhood schools and other than neighbourhood schools could be described to be somewhat flipped in comparison to the prior system. The children of mostly upper-class parents leave neighbourhood schools, particularly general classrooms, to enter selective classes, while the rest of the children attend to neighbourhood school. Today, upper-class children and children with severe support needs leave neighbourhood schools and classrooms, and the rest stay.